A FRAMEWORK TO SUPPORT STUDY GROUP FORMATION USING ONLINE SOCIAL MEDIA -THE CASE OF TWITTER - Omuya, Erick Odhiambo (My University, 2014)
Online social media has positioned itself as one of the best media of communication and information sharing. People are able to write short messages on their walls using various social media like Twitter, Facebook, Bebo, hi5 and Ibibo. Through these messages they share and discuss about things like news, jokes and what they are going through. The short messages are generally called status updates and specifically tweet when you are using tweeter. Tweets have become so important in the world of information and communication because they have a great potential to pass information very fast. The knowledge generated from twitter has however not been adequately harnessed and utilized as it ought. The purpose of this study was to develop a way of searching, filtering, organizing and storing the information from social media so that it can be put to some good use. The social media in itself does not have the ability to facilitate harnessing and utilizing of the information that passes through it. This research therefore addressed this limitation by using the social media to cluster students and by so doing supported group learning. After being developed, the prototype was evaluated at the Nairobi Institute of Business Studies with a group of twenty students being involved. The tools for data collection that were used included interviews and questionnaires the interviews especially for requirements gathering and system evaluation. The users interacted with the prototype for a period of two weeks and evaluated it based on usability and functionality. All the students involved in the evaluation had twitter accounts. Most of them used twitter for social purposes while very few used it for academic reasons. The system was generally simple to use and so most of the users were comfortable with it. The users’ response on functionality and usability of the prototype was generally positive. This study only covered development of a framework for forming groups so that current and new learners can easily get involved in academic discussion. The framework however did not capture how actually discussions can be done and facilitated. This is a component that would call for further discussion. The data in this study was descriptively analyzed.